Zahar Prilepin’s blogs as the new modern literary creativity measurement - Karwacka, Monika (Slavia Centralis, 2020)
BLOGI ZAHARJA PRILEPINA KOT NOVO MERILO SODOBNE LITERARNE USTVARJALNOSTI Modern technological development affects literature not only in the form of perception and reading books but also in the way writers create and publish their literary pieces of art. Prilepin, as a famous and popular contemporary writer with a confirmed position in the Russian literary environment, promotes his books and Russian literature using internet blogs. The author attempts to analyse his blogs and other internet resources in order to show Prilepin’s involvement in creating e-literature. Contemporary blogs are explained in the context of the public literary sphere, which creates unique social opportunities in social communication. The activities of writers and literary critics who have a well-established position in the literary environment appear to have an undeniably significant impact on the revolution in Russian web literature that is represented by a new genre of literature, which is expressed in the wide distribution of literary works over the internet and the interactive communication of the author with readers and their direct influence on the author’s further creativity.